Vulneración de los derechos del Tercero ajeno a la relación obligacional, respecto a la oponibilidad al cambio de domicilio - Espinoza Cardenas, Maikol Frank (2019)
ABSTRACT The present investigation entitled: "Vulneration of the rights of the Third party to the obligational relationship, regarding the oponibility to the change of address" seeks to measure the scope of vulnerability that the figure of the opposability to the change of domicile entails, from the perspective of the third party outside the mandatory relationship, call owners, tenants, family, etc., who are affecting their constitutional rights to peace, tranquility by creditors, a situation that leads third parties to resort to the Judiciary, claiming that debtors They no longer live at home, through requests for return of identity card. Under this perspective, the study of judicial files processed by the Leon XIII Savings and Credit Cooperative before the Justice of the Justice of the Superior Court of Justice of La Libertad in the periods 2016-2017 was carried out. Likewise, a documentary study based on doctrinal sources was carried out, opinions of specialists in civil, commercial and constitutional law were used, to whom surveys, interviews were applied, seeking to give an integral solution to the problem posed. From the discussion of the results, it was observed that the Judges, when evaluating a request for the return of the identity card by third parties outside the compulsory relationship, define their pronouncement as to whether or not the debtor communicated the change of domicile to his creditor through communication unquestionable, in order to declare the returns of identification cards unfounded or inadmissible, leaving aside the prerogative that assists him in application of the second paragraph of article 40 of the Civil Code. The limited knowledge of how to apply the figure of enforceability to the change of domicile, by the third party outside the mandatory relationship, emanated from the deficient wording of article 40 of the Civil Code, creates confusion to jurisdictional operators by not establishing any appropriate procedure for legal effects against creditors and the judiciary.